Balanced Scorecard: Strategy Towards World Class University - Junusi, Rahman El; Musahadi, Musahadi; Yuningrum, Heny (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
The purpose of this research is how to implement the Balanced Scorecard (BSC) at UIN Walisongo in an effort towards world class university (WCU). The research design is policy research using explorative descriptive analysis techniques. The results show that in perspective (1) changes in research organizations: international collaborative research and international publications need to be improved, (2) human resource policies, increasing the number of professors and doctors and staff education, based on educational qualifications are still limited (3) academic programs, international accredited study programs need to be started, (4) Internal Governance, as an anti-corruption campus that applies the best Integrity zone in PTKI and (5) Funds, develops and explores funding sources from domestic and foreign partners to strengthen the internationalization program towards WCU.Tujuan penelitian adalah bagaimana implementasi BSC pada UIN Walisongo dalam upaya menujuÂ world class university (WCU). Desain penelitian adalah penelitian kebijakan dengan menggunakan teknik analisis deskriptif eksploratif. Hasil penelitian menunjukkan bahwa dalam perspektif (1) perubahan organisasi: penelitian,Â masih terbatasnyaÂ penelitian kolaboratif internasional dan publikasi internasional, (2) kebijakan sumber daya manusia, meningkatkan jumlah profesor dan doktor dan pendidikan staf, berdasarkan kualifikasi pendidikan masih terbatas (3) program akademik, program studi terakreditasi internasional perlu dimulai, (4) Tata Kelola Internal, sebagai kampus anti-korupsi yang menerapkan zona Integritas terbaik di PTKI dan (5) Dana, mengembangkan dan mengeksplorasi sumber pendanaan dari mitra domestik dan asing untuk memperkuat program internasionalisasi menuju WCU.